The membership and programs of the IGY Participating Committees - Nicolet, M. (Annals of the International Geophysical Year ;, 1959)
Annals of the International Geophysical Year, Volume 9: The Membership and Programs of the IGY Participating Committees contains a list of the programs as prepared at the beginning of the IGY. The number of programs increased during the IGY preparatory period when the number of Committees, amounting to 22 in 1953, increased to 35 in 1954, 40 in 1955, 50 in 1956 and 67 when the IGY began on July 1, 1957. The list of Committees shows the growth of the participation in the IGY. This book is divided into 67 chapters. Each chapter covers the contributions and research works in the IGY of each count.